Strengths use and work engagement: a weekly diary study. Issue 3 (3rd May 2016) - van Woerkom, Marianne; Oerlemans, Wido; Bakker, Arnold B.
Abstract : The present study among 65 civil engineers investigates the impact of organizational support for strengths use on weekly work engagement and proactive behaviour. Positive psychology postulates that strengths use makes people feel authentic and efficacious. We argue that employees use these positive psychological states as resources that fuel work engagement and proactive work behaviour. Participants completed a general questionnaire regarding strengths use support, and a weekly quantitative diary questionnaire regarding their strengths use, self-efficacy, work engagement, and proactive behaviour over a period of five consecutive workweeks. In line with the hypotheses, the results of multilevel structural equation analyses showed that organizational strengths use support was positively related to weekly strengths use. Furthermore, the results indicated that weekly strengths use was positively related to weekly work engagement and proactive behaviour, through weekly self-efficacy (sequential mediation). Although strengths use support contributed indirectly to work engagement (mediated by strengths use and self-efficacy), there was no significant indirect relationship with proactive behaviour. Our study indicates that strengths use is associated with employees' levels of self-efficacy, work engagement, and proactive behaviour and that organizations can help employees to use their strengths more often by giving them the opportunity to do what they are good at.